2007
DOI: 10.1002/cbic.200600522
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplexed Protein Kinase Assay

Abstract: We report a novel protein kinase assay designed for high-throughput detection of one or many kinases in a complex mixture. A solution-phase phosphorylation reaction is performed on 900 different peptide substrates, each covalently linked to an oligonucleotide tag. After incubation, phosphoserine, phosphothreonine, and phosphotyrosine are chemically labeled, and the substrates are hybridized to a microarray with oligonucleotides complementary to the tags to read out the phosphorylation state of each peptide. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Shults et al reported carbodiimide-mediated, selective formation of a covalent bond between a fluorescent dye derivative and the phosphate moiety of phosphopeptides generated by incubation with kinases [145]. Alternatively, Akita et al used base-mediated ß-elimination to transformed cellulose surface-bound phosphopeptides generated by protein kinase A selectively into dehydroalanine-containing peptides which could be labelled with fluorescence dye derivatives [146].…”
Section: Assays and Detectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Shults et al reported carbodiimide-mediated, selective formation of a covalent bond between a fluorescent dye derivative and the phosphate moiety of phosphopeptides generated by incubation with kinases [145]. Alternatively, Akita et al used base-mediated ß-elimination to transformed cellulose surface-bound phosphopeptides generated by protein kinase A selectively into dehydroalanine-containing peptides which could be labelled with fluorescence dye derivatives [146].…”
Section: Assays and Detectionmentioning
confidence: 97%
“…The peptide nucleic acid tag encodes the structure of the attached peptide derivative and, therefore, allows spatially addressed deconvolution after hybridization to Affymetrix GenFlex oligonucleotide microarray. This approach was extended to the profiling of enzymatic activities of proteases [66,174,180,181] and kinases [67,145] using PNA/DNA-encoding. The use of oligonucleotides and in particular peptide nucleic acids (PNAs) to encode libraries was reviewed comprehensively [182].…”
Section: Assays and Detectionmentioning
confidence: 99%
“…There is no need to sequence the peptides, because the amino acid sequences of peptides immobilized in each array are already known. Several techniques other than radioisotope incorporation can be utilized for detection and quantification of phosphorylated peptides, i.e., fluorescence-labeled anti-pY antibody [64], a fluorescent phosphosensor dye [65,66], surface plasmon resonance with a zinc(II)-chelating compound [67], and matrix-assisted laser desorption/ionization (MALDI) mass spectrometry [68].…”
Section: Other Peptide Array-based Approachesmentioning
confidence: 99%
“…Other types of soluble peptide libraries were prepared by individual coupling of peptides with DNA [232,233] or peptide nucleic acid [234] tags. After biotransformation of the peptide library in the solution assay (cleavage by protease, phosphorylation by kinase), the modified substrate was captured on a complementary DNA array and the structure of the substrate peptide was defined.…”
Section: Synthesis Of Peptide Mixturesmentioning
confidence: 99%